Keabsahan dan Perlindungan Hukum Perjanjian Kerjasama Influencer dengan Platform Media Sosial - Jinoto, Devin (Peradaban Journal of Law and Society, 2025)
This research analyzes the validity of the subject matter of the agreement, intellectual property rights (IPR) protection, as well as ethical issues and legal certainty in the cooperation agreement between influencers and social media platforms. Using a normative legal research method with legislative and conceptual approaches, this study aims to understand the legal aspects governing the relationship between influencers and platforms in the context of digital marketing. The main focus of this research is on the fulfillment of the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code (KUHPerdata), and the necessity for clarity and transparency regarding the subject matter of the agreement, such as digital content and promotional services. The research also explores the potential violations of intellectual property rights by both the platform and the influencer, including the unauthorized use of content and plagiarism. The issue of imbalance in negotiating positions, where influencers are generally weaker compared to the platforms with greater bargaining power, is a key point of focus in this discussion. The study recommends enhancing transparency in agreements, standardizing intellectual property protection clauses, and harmonizing regulations related to digital contracts and consumer protection. Overall, the research concludes that improvements in the legal framework governing these collaborations are necessary to create a fairer environment and provide legal certainty for all parties involved. Penelitian ini menganalisis keabsahan objek perjanjian, perlindungan hak kekayaan intelektual (HKI), serta isu etika dan kepastian hukum dalam perjanjian kerjasama antara influencer dan platform media sosial. Menggunakan metode penelitian hukum normatif dengan pendekatan legislatif dan konseptual, penelitian ini bertujuan untuk memahami aspek-aspek hukum yang mengatur hubungan antara influencer dan platform dalam konteks pemasaran digital. Fokus utama penelitian ini adalah pada pemenuhan syarat sah perjanjian menurut Pasal 1320 Kitab Undang-Undang Hukum Perdata (KUHPerdata), serta perlunya kejelasan dan transparansi terkait objek perjanjian, seperti konten digital dan layanan promosi. Penelitian juga mengeksplorasi potensi pelanggaran HKI baik oleh platform maupun influencer, termasuk penggunaan konten tanpa izin dan plagiarisme. Isu ketidakseimbangan posisi negosiasi, di mana influencer cenderung lebih lemah dibandingkan dengan platform yang memiliki kekuatan tawar lebih besar, menjadi sorotan utama dalam pembahasan ini. Penelitian ini merekomendasikan peningkatan transparansi dalam perjanjian, standarisasi klausul perlindungan HKI, serta harmonisasi regulasi yang berkaitan dengan kontrak digital dan perlindungan konsumen. Secara keseluruhan, penelitian ini menyimpulkan bahwa perbaikan dalam kerangka hukum yang mengatur kerjasama ini diperlukan untuk menciptakan lingkungan yang lebih adil dan memberikan kepastian hukum bagi semua pihak yang terlibat.